Developing future clinical leaders for quality improvement: experience from a London children's hospital. Issue 11 (9th July 2013) - Runnacles, Jane; Moult, Beki; Lachman, Peter
Abstract : Introduction: Medical training does not necessarily prepare graduates for the real world of healthcare in which continual improvement is required. Doctors in postgraduate training (DrPGT) rarely have the opportunity to develop skills to implement changes where they work. Paradoxically they are often best placed to identify safety and quality concerns and can innovate across organisational boundaries. In order to address this, educational programmes require a supportive educational environment and should include experiential learning on a safety and quality project, alongside teaching of quality improvement (QI) knowledge and systems theory. Method: Enabling Doctors in Quality Improvement and Patient Safety (EQuIP) has been designed for DrPGT at a London children's hospital. The aim is to prepare trainees for the future of continual improvement to ensure safe and effective services are developed through effective clinical microsystems. This paper describes the rationale and design of EQuIP with evaluation built in the evolving programme. EQuIP supports DrPGTs through a QI project within their department, aligned to the Great Ormond Street NHS Foundation Trust's objectives. This changes the way DrPGTs view healthcare as they become quality champions for their department. A three-level approach to the programme is described. The innovation involves a peer-designed programme while being work-based, delivering organisational strategies. Results: Results of the preprogramme and postprogramme evaluations demonstrate an improvement in knowledge, skills and attitudes. Benefits to both the DrPGTs and the organisation are emphasised and key factors to achieve success and barriers identified by the participants. Discussion: The design and evaluation of EQuIP may inform similar educational programmes in other organisations. This capacity building is crucial to ensure that future clinical leaders have the skills and motivation to improve the effectiveness of clinical microsystems.